Effects of Hydrogen Peroxide and Methyl Eugenol on Fruit Growth, Yield and Fruit Fly Infestation of Syzygium Samarangense - Moneruzzaman Khandaker, Mohammad; Zuriani Ismail, Siti; Hafiza, Nurul; Mat, Nashriyah; Ngah, Norhayati (International Journal of Engineering and Technology, 2018)
A study was conducted to investigate the effects of hydrogen peroxide (H2O2) and methyl eugenol (ME) on fruit growth, yield and fruit fly infestation of wax apple (Syzygium samarangense var Jambu madu). The selected experimental tree branches were either left untreated or sprayed with 20 mM H2O2, 20 mM H2O2 plus ME or ME alone under field condition. The results showed that combine treatment of H2O2 and ME increased the net photosynthetic rate, CO2 assimilation, stomatal conductance and internal CO2 concentration of wax apple leaves. In addition, fruit weight, fruit firmness and TSS content of wax apple fruits significantly improved with H2O2 and ME treatment. The application of Methyl eugenol alone or combined with H2O2 reduced the number of fruit fly in wax apple fruits. There was positive correlation between fruit fly infestation and fruit size and between fruit fly infestation and fruit sweetness (TSS content) in H2O2 and Methyl eugenol treated fruits. Besides, we recorded negative correlation between the fruit fly infestation and firmness of treated wax apple fruits. It was concluded that application of hydrogen peroxide and methyl eugenol stimulated fruit growth and reduced the fruit fly infestation on wax apple under field condition.Â Â